Risk behaviors and awareness on cardiovascular diseases and cancer among the Filipino adults a mutilevel analysis - Tolentino, Maria Leda T.
Cardiovascular diseases and cancer have become two of the leading public health concerns in the Philippines today. These conditions have been classified as members of a group of disorders known as "lifestyle-related diseases" because of their known associations with risk behaviros, cuch as smoking and dietrary fat consumption. OBJECTIVES: 1) to determine the factors affecting the level of knowledge/awreness on cardiovascular diseases and cancer among Filipino adults across the country, and 2) to determine the individual/internal and environmental factors affecting the dietrary pattern and current smoking behavior of Filipino adults. METHODS: The study utilized secondary data that had been collected from the nationwide survey conduected for the purpose of evaluation of the lifestyle-related disease prevention and control programs implemented by the Department of Health. The method utilized for data analysis was hierarchical linear and non-linear modeling. RESULTS: There was insufficient evidence to prove that there is a relationship between the extent of implementation of the health education interventions and the individual's level of knowledge on CVD and cancer, for both the female and male population. On the other hand, the study found that among male Filipinos, the level of knowledge on CVD are related to the odds of being a current smoker, but the values may be too small to warrant clinical significance. Meanwhile, those Filipino adults, either male or female, who have higher levels of knowledge on cancer and CVD, tend to consume more fat in their weekly diet. Residing in a city or province was not found to be significantly related to the amount of fat consumed by a Filipino adult per week. CONCLUSIONS: The findings of the study suggest that there could be stronger influences on the Filipino's smoking behavior and fat consumption, which outweighs his knowledge on the ill efects of these risk behaviors. Furthermore, the results imply that health promotion strategies in preventing and changing risk behaviors of Filipino adults should be adapted to take into account not only improvement in awareness on diseases and its risk factors, but also the behavior modification techniques that could directly target the risk behaviors, such as motivation to change and self-control.